(untitled) (Journal of Nepalese Business Studies, 2006)
The students of BBS program of Tribhuvan University (T.U.) must carry out a fieldwork study of two weeks by visiting the organizations or projects. The results of past years show that students are not able to follow the requirement of Faculty of Management in writing the report of their fieldwork. So this study attempts to uncover the common mistakes and their causes while writing the fieldwork report. Students were found moderate in writing the fieldwork report. They lack the habit of reading related books; do not get appropriate, effective, and intensive orientation to equip themselves with research skills. Journal of Nepalese Business Studies Vol.1(1) 2004 pp.75-80